Investigation of strain-rate effect on the compressive behaviour of closed-cell aluminium foam by 3D image-based modelling. (5th January 2016) - Sun, Yongle; Li, Q.M.; Lowe, T.; McDonald, S.A.; Withers, P.J.
Abstract: Three-dimensional (3D) finite element models based on computed tomography (CT) images are developed to investigate the strain-rate effect on the compressive behaviour of closed-cell aluminium foam (Alporas). It is found that at strain-rates below shock conditions the rate dependence of the cell–wall material is the main cause of the strain-rate hardening of the compressive strength of Alporas foam. The foam exhibits slightly higher strain-rate sensitivity than that of the cell–wall material due to localised strain-rate amplification in some critical load-bearing elements. By contrast, the micro inertia of individual cell walls associated with the nonuniform deformation of Alporas foam has a negligible contribution. Under shock conditions the stress measured at the loading end is always enhanced, but the stress measured at the supporting end is complicated, depending on the characteristics of the contiguous cells. In general, shock leads to a concentrated large deformation in the cells at the loading end, but a restrained small deformation in the cells at the supporting end. Consequently, the hardening effect of the rate dependence of cell–wall material on the supporting stress becomes constrained with further increasing strain-rate, and the supporting compressive strength is limited to the quasi-static level when the cell–wall material is rate-independent. Graphical abstract: Highlights: Image-based modelling is employed to clarify the meso-scale mechanism for the strain-rate sensitivity of aluminium Alporas foam. The rate dependence of cell–wall material is the main cause of the strain-rate hardening of compressive strength. Micro inertia has a negligible contribution. Shock enhances the loading stress, but has complicated effect on the supporting stress.